Influence of fire retardant additives on fire properties of materials based on polyester resin polimal 1033 APy - Gałaj, Jerzy; Półka Marzena; Šukys, Ritoldas (Journal of Civil Engineering and Management, 2013)
To investigate the influence of special additives – fire retardants – on the selected fire properties of materials based on polyester resin Polimal 1033 APy produced in the chemical plant ‘Organika-Sarzyna’ in Poland, a full scale of fire methods has been used. Three samples have been studied during combustion in a closed compartment: an unmodified sample, a sample containing 14% of MoO3 (molybdenum trioxide) and a sample containing 14% of antimony trioxide (Sb2O3). Several important parameters related to the combustion of tested polyester materials have been obtained as a result of the undertaken studies such as temperature and carbon monoxide (CO) concentration. This paper discusses the outcome of the conducted full-scale studies. Special emphasis is placed on analysis showing variation in time of these parameters during the combustion of three different polyester materials with and without fire retardant additives. One of the most important parameters taking into account evacuation conditions is time, for reaching the critical value of both temperature and CO concentration that has also been considered in the study. The performed research has demonstrated that the application of the selected additives in the polyester material, in our case Polimal 1033 APy, has enhanced fire resistance of the material mainly by a significant delay of a growth in temperature and CO concentration and almost twice-reduced CO generation, particularly in the case of adding Sb2O3.